2013
DOI: 10.1186/1476-4598-12-155
|View full text |Cite
|
Sign up to set email alerts
|

A TrkB–STAT3–miR-204-5p regulatory circuitry controls proliferation and invasion of endometrial carcinoma cells

Abstract: BackgroundWe previously identified TrkB as an oncogene involved in promoting metastasis in endometrial carcinoma (EC). Here, we sought to delineate the effect of changes in TrkB expression on the global profile of microRNAs (miRNAs) in EC cells and further investigated the correlation between the expression of certain miRNA and TrkB in the clinicopathologic characteristics of EC patients.Methods and resultsUsing quantitative reverse transcription-PCR (qRT-PCR), we found that expression of TrkB mRNA has no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 57 publications
7
122
1
2
Order By: Relevance
“…42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma. 43 Imam et al 44 showed that the genomic locus encoding miR-204 is frequently lost in multiple cancers, including breast and ovarian cancers, and pediatric renal tumors. They suggest that miR-204 targets distinct genes involved in tumorigenesis including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma. 43 Imam et al 44 showed that the genomic locus encoding miR-204 is frequently lost in multiple cancers, including breast and ovarian cancers, and pediatric renal tumors. They suggest that miR-204 targets distinct genes involved in tumorigenesis including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have shown that miR-204 is downregulated in multiple human cancers (7,(15)(16)(17)(18)(19)(20)(21)(22)(23). CpG methylation represents an important mechanism responsible for the inactivation of genes, including miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-204 has been reported to function as a tumor suppressor in a variety of human cancers through different mechanisms (15)(16)(17)(18)(19)(20)(21)(22)(23), suggesting its extensive function in tumorigenesis. For example, miR-204 inhibited tumor growth in renal clear cell carcinoma (17) and pancreatic cancer (32) and suppressed invasion in endometrial cancer (23), glioma (21), gastric cancer (16), intrahepatic cholangiocarcinoma (16), and head and neck tumor (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more important was the global change in the physiology of these cells forced by etoposide toward acquirement of the CSC status. In addition, the analysis and validation of iCSC microRNAs isolated from 79HF6 glioblastoma cells revealed a subtle deregulation of different miRNAs such as miR204-5p known to contribute to tumor aggressiveness and metastatic behavior (Díaz-Carballo et al, 2008b;Bao et al, 2013;Qiu et al, 2013). We decided to take a descriptive rather than analytic approach to the miRNA results, as the understanding of the function of the studied representatives and this field in general is still evolving (Fig.…”
Section: Biochemical Features Of Resistant Tumor Cell Entitiesmentioning
confidence: 99%